Transformasi Pengelolaan Aset UMKM: Inovasi Menuju Kinerja Keuangan Berkelanjutan - Dwiyani Sudaryanti; Mohamad Bastomi (Universitas Nurul Jadid, 2025)
Effective asset management is expected to be a driving force for the Malang City Government in achieving its target of upgrading 4,000 MSMEs. Failure to manage assets properly results in waste and decreased business productivity. This community service program aims to provide business owners in Malang City with practical knowledge and skills on how to manage assets efficiently and in a structured manner. This training program aims to provide practical knowledge and skills to business actors in Malang City in managing assets efficiently and structurally. More specifically, this training can form simple and practical calculation methods that can be applied sustainably in MSMEs in Malang City. This program uses a service learning method consisting of the stages of socialization, education, training, and evaluation. In the education stage, participants were given an understanding of asset management theory supported by relevant literature so that they could apply the concepts in business. The training focused on the practical use of Excel formats for recording inventory, supplies & equipment, and fixed asset management. Evaluation was carried out using pre-tests and post-tests, which showed a significant improvement in asset management skills. Although this program was successful, there were obstacles such as time constraints and variations in participants' understanding of technology. This program made a scientific contribution not only by enriching the literature on the application of service learning in the context of community service, but also by offering practical solutions for using Excel in calculating the value of MSME assets. The evaluation results showed an average increase of 45% in asset management skills among female culinary entrepreneurs in Malang City after participating in the training.